Efects of extracts of green manure in Lactuca sativa and Digitaria horizontalis - Erasmo, Eduardo Andrea Lemus; de Azevedo, Waldeon Reis; da Costa, Neumárcio Vilanova; Alves, Pedro Luis da Costa Aguiar [UNESP] (FapUNIFESP (SciELO), 2011)
This study aimed to evaluate the potential allelopathic efects of four species of green manure (Canavalia ensiformis, Crota-laria spectabilis, Mucuna aterrima and Sorghum bicolor cv. AG 2005) on the seed germination and initial growth of seedlings of Lactuca sativa and Digitaria horizontalis. In the frst experiment, the efects of dilute solutions of 1%, 2%, 3%, 4%, 5% and 10% of shoot and root aqueous extracts of green manure were evaluated on germination, speed of germination index (SGI) and root length of L. sativa. In the second experiment, the incorporation into the soil of 0, 10, 20, 30, 40 and 50 g dm-3 of biomass of green manure was evaluated on the accumulation of dry weight (shoots and roots) and root development of seedlings of L. sativa and D. horizontalis. In conclusion, the aqueous extracts of the species C. ensiformis, C. spectabilis, M. aterrima and S. bi-color cv. AG 2005 promoted negative allelopathic efects on seed germination and SGI of L. sativa. The incorporation into the soil of the biomass also negatively afected the initial development of seedlings of L. sativa. However, there were benefcial allelopathic efects on the early development of D. horizontalis with incorporation into the soil biomass of C. spectabilis.
Efeito de extratos de adubos verdes sobre Lactuca sativa e Digitaria horizontalis
Keywords: Allelochemicals; Fabaceae; Germination; Weed